2021
DOI: 10.29303/jbt.v21i2.2666
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany Study of Medicinal Plants by the Mbojo Tribe Community in Ndano Village at the Madapangga Nature Park, Bima, West Nusa Tenggara

Abstract: One of the cultural characteristics of people in developing countries is that traditional elements are still dominant in everyday life. These activities include the use of plants as medicinal ingredients by various ethnic groups or groups of people living in rural areas, one of which is the Mbojo Tribe, Ndano Village in Madapangga, Bima Regency, NTB. This study aims to identify the types of medicinal plants and to describe the local wisdom of the Mbojo Tribe in Ndano Village regarding the use of medicinal plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
4
1
4
Order By: Relevance
“…The abundance of shrubs in the study area could explain the high usage of shrubs. These findings contradict Ani et al (2021), who discovered that trees were the dominant species for herbal medicine in Ndano village, West Nusa Tenggara. According to respondents, shrubs are grown in home gardens due to their small size, and in addition to being medicinal plants, several species are used as food and ornamental plants.…”
Section: Growth Form and Plant Parts Usedcontrasting
confidence: 58%
“…The abundance of shrubs in the study area could explain the high usage of shrubs. These findings contradict Ani et al (2021), who discovered that trees were the dominant species for herbal medicine in Ndano village, West Nusa Tenggara. According to respondents, shrubs are grown in home gardens due to their small size, and in addition to being medicinal plants, several species are used as food and ornamental plants.…”
Section: Growth Form and Plant Parts Usedcontrasting
confidence: 58%
“…This is likely because the search and mode of use of this plant group are easy besides the therapeutic indication of its medicinal properties (Baydoun et al 2015;Bahadura et al 2020). However, a study conducted in Aceh Tamiang District reported that the dominant medicinal plants were shrubs (33%) and Ani et al (2021) found that trees were the dominant medicinal plant species in Ndano village, West Nusa Tenggara. The variation in the use of ethnomedicine based on the growth form of this medicinal plant can depend on differences in environmental conditions, belief systems in socio-cultural aspects, and medical practices in various regions and countries.…”
Section: Growth Form and Plant Parts Usedmentioning
confidence: 97%
“…Each ethnic group in Indonesia has its unique knowledge of how to use diverse biological resources, including for medication and health care. Ethnobotanical knowledge of medicinal plants has long been owned by local communities across Indonesia (Ani et al 2021), and this tradition was established by the people of Kalimantan and subsequently promoted by the people of Java (Nurrani et al 2015). The community's knowledge and skills in the usage of traditional medicinal herbs have been passed down through oral storytelling from generation to generation and have been preserved till now (Suwardi et al 2021;Navia et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Bahan tersebut terdiri dari cabe jawa, cengkeh, kunyit, temulawak, jahe, lempuyang, temu giring, pucuk daun jambu, bawang putih, kadara atau buah gorek, dan buah pinang. Secara empiris jamu ini dimanfaatkan sebagai penambah stamina, menurunkan kolestrol, pemeliharaan kesehatan, dan penambah nafsu makan (Ani et al, 2021).…”
Section: Pendahuluanunclassified